SELF-EFFICACY AND PERCEPTION OF THE TEACHING PROFESSION: KEY FACTORS IN ENHANCING STUDENTS’ INTEREST IN BECOMING TEACHERS - Aulia, Fitrah; Syahrul, Syahrul; Sappaile, Baso Intang; Ishak, Suryadi (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
Interest in pursuing a career as a teacher is an important factor in the preparation of future educators, especially in teacher education programs. Preparation of future educators, especially in teacher education programs. The objectives of this study are 1) to determine the effect of self-efficacy and perceptions of the teaching profession on interest in becoming a teacher in chemistry education study program students, 2) to determine the effect of self-efficacy on interest in becoming a teacher of chemistry education study program students, 3) to determine the effect of perceptions of the teaching profession on interest in becoming a teacher of chemistry education study program students. A quantitative correlational approach was used, with participants selected through proportional random sampling. Independent variables include self-efficacy (X1), which represents students' confidence in their teaching skills, and perceptions of the teaching profession (X2), which includes attitudes towards the profession's image, challenges, and social significance. The dependent variable was students' interest in pursuing a career as a teacher (Y). A questionnaire was used to collect data, and its reliability was assessed using Cronbach's Alpha, construct validity with Pearson's product-moment correlation, and content using Gregory's model. The impact of the independent variables on the dependent variable was evaluated using regression analysis. The results showed that student's motivation to pursue a career in teaching is strongly influenced by their opinions about the teaching profession and their level of self-efficacy.